Comparison of the effect of soil pollution sources on soil magnetic susceptibility in metropolitan cities (Case study: District 6, Tehran) - Farnaz Ghobadi; Shahrzad Khoramnejadian; Sadraldin Alipour (آلودگی‌های محیطی و توسعه پایدار شهری)
Pollutants enter the soil from various sources and affect its physicochemical properties. The presence of heavy metals in the soil increases the likelihood of their entry into the food chain. Industrial and transportation sources play a major role in the introduction of these metals into the soil. The aim of this study, conducted in 2021 in District 6 of Tehran Municipality, was to determine the relationship between the accumulation of heavy metals from various sources and the magnetic susceptibility of the soil. For this purpose, 18 points were randomly selected across different parts of the region for sampling. The amounts of heavy elements (chromium, cadmium, lead and arsenic) were measured using an atomic absorption spectrometer, and magnetic susceptibility was also assessed at these locations. The highest level of soil contamination was related to lead (38 mg/kg), while the lowest was related to cadmium (<0/04 mg/kg). The results showed no correlation between magnetic susceptibility and the density of organic matter particles. Magnetic susceptibility was not correlated with chromium, but showed a direct relationship with cadmium and arsenic, and an inverse relationship with lead.